Perinatal transmission of hepatitis C antigens: envelope 1, envelope 2 and non-structural 4. Issue 8 (August 2015) - Attallah, Abdelfattah M.; Abdallah, Sanaa O.; El-Far, Mohamed; Omran, Mohamed M.; Tabll, Ashraf A.; Ghaly, Mohamed F.; Ezzat, Said M.; Elhamshary, Manal O.; El-Gohary, Zeinab M.; Mohamedin, Attiya H.; El-Morsi, Adel A.; Askora, Ahmed A.; et al.
Abstract: Background: Perinatal exposure to hepatitis C virus (HCV) antigens during pregnancy may affect the developing immune system in the fetus. We aimed to study the perinatal transmission of HCV structural and non-structural antigens. Methods: Sera from 402 pregnant mothers were tested for anti-HCV antibody and HCV RNA. HCV antigens were determined in sera from 101 HCV-infected mothers and their cord blood. Results: In both serum and cord blood samples, HCV NS4 (non-structural 4) at 27 kDa, E1 (envelope 1) at 38 kDa and E2 (envelope 2) at 40 kDa were identified, purified and quantified using western blotting, electroelution and ELISA. Maternal sera and neonate cord blood samples had similar detection rates for NS4 (94.1%), E1 (90.1%) and E2 (90.1%). The mean maternal serum levels (optical density, OD) of HCV NS4 (0.87 ± 0.01), E1 (0.86 ± 0.01) and E2 (0.85 ± 0.01) did not differ significantly ( p > 0.05) from those of neonatal cord blood (0.83 ± 0.01, 0.87 ± 0.01 and 0.85 ± 0.01, respectively). Also, strong correlations ( p < 0.0001) were shown between sera and cord blood sample levels of HCV NS4, r = 0.77; E1, r = 0.76 and E2, r = 0.80. The vertical transmission of these antigens in vaginal delivery did not differ significantly ( p > 0.05) from those in caesarean section. Conclusions: These findings indicate that vertical transmission of HCV NS4, E1 and E2 antigens was very high. Thus, exposure to these antigens may influence the developing immune responses to natural infection or future vaccination.